Radioiodination and Purification of [131I]β-CIT and [131I]FP-CIT with an Automated Radiosynthesizer - Elisabeth Plhak; Edith Gößnitzer; Reingard M. Aigner; Herbert Kvaternik (MDPI AG, 2022)
Dopaminergic transporter (DAT) imaging with single photon emission computed tomography (SPECT) is used to diagnose Parkinson's disease and to differentiate it from other neurodegenerative disorders without presynaptic dopaminergic dysfunction. The radioiodinated tropane alkaloids [123I]FP-CIT and [123I]β-CIT enable the evaluation of the integrity of DATs. Commonly, the labeling of these compounds is performed by electrophilic substitution of the alkylstannylated precursors with radioactive iodine and following purification by HPLC or solid phase extraction (SPE). This work presents the first radioiodination of β-CIT and FP-CIT with no carrier added [131I]NaI on a Scintomics GRP synthesis module. Free iodine-131 and impurities were removed by SPE over a C-18 Sep-Pak cartridge. We achieved a radiochemical yield of >75% and a radiochemical purity of >98% with both compounds. Our development of an automated synthesis on a commercially available synthesizer ensures robust and efficient labeling of [131I]FP-CIT and [131I]β-CIT starting with low concentrated radioiodine.